2016
DOI: 10.1186/s12944-016-0322-4
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted high-density lipoproteins promote wound repair and blood flow recovery in response to ischemia in aged mice

Abstract: BackgroundThe average population age is increasing and the incidence of age-related vascular complications is rising in parallel. Impaired wound healing and disordered ischemia-mediated angiogenesis are key contributors to age-impaired vascular complications that can lead to amputation. High-density lipoproteins (HDL) have vasculo-protective properties and augment ischemia-driven angiogenesis in young animals. We aimed to determine the effect of reconstituted HDL (rHDL) on aged mice in a murine wound healing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…The first report that showed that high-density lipoproteins (HDL) can help to achieve this therapeutic goal came from Gordts et al (2014) [12], who demonstrated that topical administration of HDL gel improved delayed (splinted) wound healing in hypercholesterolaemic apolipoprotein (apo)E −/− mice. This finding resonates with reports that exposure to HDL can promote the proliferation of endothelial progenitor cells, aiding wound healing of the arterial wall in hypercholesterolaemic rats [13], and promote wound repair, rescue blood flow and promote neovessel formation due to ischaemia [14,15]; dysfunctional HDL, which arises in a number of disease states, impairs re-endothelialisation in vitro and in vivo [16][17][18][19]. Apolipoprotein (apo) A-I, the major protein component of HDL, and apoA-I mimetics can also promote arterial healing by reducing oxidative stress [20], and protect against impaired re-endothelialisation due to dysfunctional HDL [21], although it cannot entirely replicate the effect of HDL [22].…”
Section: Introductionsupporting
confidence: 87%
“…The first report that showed that high-density lipoproteins (HDL) can help to achieve this therapeutic goal came from Gordts et al (2014) [12], who demonstrated that topical administration of HDL gel improved delayed (splinted) wound healing in hypercholesterolaemic apolipoprotein (apo)E −/− mice. This finding resonates with reports that exposure to HDL can promote the proliferation of endothelial progenitor cells, aiding wound healing of the arterial wall in hypercholesterolaemic rats [13], and promote wound repair, rescue blood flow and promote neovessel formation due to ischaemia [14,15]; dysfunctional HDL, which arises in a number of disease states, impairs re-endothelialisation in vitro and in vivo [16][17][18][19]. Apolipoprotein (apo) A-I, the major protein component of HDL, and apoA-I mimetics can also promote arterial healing by reducing oxidative stress [20], and protect against impaired re-endothelialisation due to dysfunctional HDL [21], although it cannot entirely replicate the effect of HDL [22].…”
Section: Introductionsupporting
confidence: 87%
“…Low HDL levels are an independent risk factor for the development of type 2 diabetes mellitus (T2DM) 16 and are associated with an increased risk of microvascular disease in T2DM patients 17 . We have previously shown that HDL augments ischaemia-driven angiogenesis 18 , 19 , an effect that is retained in aged mice 20 . We recently discovered that rHDL rescues diabetes-impaired angiogenesis through its ability to increase HIF-1α stability and VEGFA production 21 .…”
Section: Introductionmentioning
confidence: 93%
“…These effects were attenuated when rHDL-treated HCAECs were exposed to the inflammatory cytokine, tumor necrosis factor α (TNFα) [ 9 ], suggesting a dichotomous role for HDL in angiogenesis. In an in vivo setting, intravenous delivery of rHDL or apoA-I in murine models of hindlimb ischemia (HLI) resulted in accelerated recovery of blood perfusion and increased capillary density in the ischemic hindlimbs [ 9 , 11 , 12 , 13 ]. Similar results were seen in a rabbit model of HLI following treatment with des-fluoro-anacetrapib, an inhibitor of cholesteryl ester transfer protein (CETP) which raises HDL levels [ 14 ].…”
Section: Introductionmentioning
confidence: 99%